Lumbosacral injection of lidocaine, detomidine and lidocaine–detomidine in goats: anti-nociceptive effects and changes on haematobiochemical parameters. Issue 1 (1st January 2020) - Zayed, Mohammed; Mahmoud, Elhussein; Khalil, Atef; Salah, Mohammed; Moustafa, Mohamed; Youssef, Mohamed; Hassaneen, Ahmed
ABSTRACT: This study was carried out to compare the analgesic effects and haematobiochemical changes produced by the administration of lidocaine, detomidine and lidocaine–detomidine combination in the epidural space of goats. All goats were assigned to all of the three different epidural treatments using a balanced crossover design with two-weeks washout period. Nociception was investigated by pinprick; times to the onset and duration of anti-nociception in the perineal region were demonstrated. Incoordination, ataxia and analgesic effects were carefully observed and recorded according to the scoring system. The blood samples for haematological and biochemical changes were collected at 0, 30, 60, 90 and 120 min post-treatment. Our results showed that detomidine treatment produced a highly significant ( P < 0.01) and ( P < 0.0001) earlier onset time than lidocaine and lidocaine–detomidine combination, respectively. Detomidine treatment had a significantly longer duration of analgesia than lidocaine ( P < 0.01) and lidocaine–detomidine combination ( P < 0.0001) treatments. Moreover, all treatments showed no effect on haematological or biochemical parameters, with no obvious systemic effects. In conclusion, administering a detomidine provided a longer duration of analgesia and a useful level of systemic sedation in goats.